PARS PLANA VITRECTOMY FOR VITREOUS HEMORRHAGE IN CIPTOMANGUNKUSUMO HOSPITAL - Razief Fitri, Marsha Alyssa; Yudantha, Anggun Rama (Indonesian Vitreoretinal Society, 2021)
Introduction: Vitreous hemorrhage is the presence of blood in the vitreous cavity. This condition could impair the visual function and hindered the clinician’s ability to examine the posterior segment of the eye. Pars plana vitrectomy (PPV) not only act as a surgical treatment of choice but also diagnostic procedure. Immediate PPV has the advantage to optimalize visual acuity Methods: Retrospective descriptive study of vitreous hemorrhage patients underwent pars plana vitrectomy in Ciptomangunkusumo Hospital, Indonesia from January to December 2018 Result: There were 160 cases of vitreous hemorrhage cases undergoes pars plana vitrectomy in 2018. Most frequent etiology was proliferative diabetic retinopathy (49.4%). Rebleeding was found only in 8 cases within the period of three months follow up. Final visual acuity was improved in majority of the cases and found to be related to timing of the surgery. Conclusion: Early vitrectomy along with systemic control of underlying factors lead to improvement of visual acuity in vitreous hemorrhage.